A generative design of collaborative innovation space - Marie Klooker; Katharina Hölzle (R&D Management, 2023)
A workplace for collaboration can be a powerful tool for fostering collaborative innovation in an organization. However, many organizations have failed in realizing the benefits of collaborative innovation workplaces. Applying a sociomaterial lens to an empirical investigation of the creation and genesis of workplaces for collaborative innovation in six organizations, we expand the focus beyond identifying workplace's material and social elements to the emergence of a collaborative innovation space as an effective workplace for collaboration. We develop a dynamic generative design model for collaborative innovation spaces. This model draws the attention to practices involved in the creation of such space instead of spatial characteristics only. It presents three dimensions for creating collaborative innovation spaces: the collaborative workplace consisting of collaborative spatial layout, work practices, and organizational structures. All are created and manifested by means of a collaborative–participatory design approach and the practice of generative reflection instead of conventional evaluation measures. Ultimately, a mindset shift is set in motion, generating a sustainable emergence of a collaborative innovation space. We conclude that a collaborative innovation space as an in-between space cannot be deliberately designed but rather evolves over time. Using our generative design model, organizations and stakeholder can actively become part of this emergence process.
Keywords: 650